Should Antiarrhythmic Treatment Be Considered Doping in a Shooting Athlete? - Castro, Renata Rodrigues Teixeira de (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Beta-blockers are prohibited for athletes competing in particular sports. This article presents a case of sick sinus syndrome in a master shooting athlete and discuss the potential shooting accuracy enhancement obtained by the treatment beyond beta-blockade.